Barriers and facilitators to implementation of developmental screening and early intervention in Canadian organizations following completion of a training and coaching model: a thematic analysis - Peterson-Katz, Karys; Piccone, Caitlin; Tuzi, Nicole; Kulkarni, Chaya; Reynolds, James N. (Frontiers in Health Services, 2023)
Developmental delay affects approximately 1 in 4 children under 6 years old. Developmental delay can be detected using validated developmental screening tools, such as the Ages and Stages Questionnaires. Following developmental screening, early intervention can occur to address and support any developmental areas of concern. Frontline practitioners and supervisors must be trained and coached to organizationally implement developmental screening tools and early intervention practice. No prior work has qualitatively investigated the barriers and facilitators to implementing developmental screening and early intervention in Canadian organizations from the perspectives of practitioners and supervisors who have completed a specialized training and coaching model. Following semi-structured interviews with frontline practitioners and supervisors, thematic analysis identified four themes: cohesive networks support implementation efforts, shared perspectives influence implementation motivation, established organizational policies increase implementation opportunities, and COVID-19 guidelines create organizational challenges. Each theme encompasses sub-themes that describe implementation facilitators: strong implementation context, multi-level multi-sectoral collaborative partnerships, adequate and collective awareness, knowledge, and confidence, consistent and critical conversations, clear protocols and procedures, and accessibility to information, tools, and best practice guidelines. The outlined barriers and facilitators fill a gap in implementation literature by providing a framework for organization-level implementation of developmental screening and early intervention following training and coaching.